2011
DOI: 10.1007/s00340-011-4756-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the surface-plasmon-induced Goos–Hänchen shifts

Abstract: Optical sensing of temperature variations is explored by studying the Goos-Hänchen (GH) lateral shift of a reflected light beam from various device based on the surface plasmon (SP) excitation at metal-dielectric interfaces. Both the Kretchman and the Sarid geometry will be considered, where the temperature variations of the GH shifts associated with excitation of both the regular and the long-range SP will be studied. It is found that while the SP-induced shifts and their temperature sensitivities are much gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…) to characterize the performance of the sensor, where DD r is the change of the GH value at the same l and DT is the value of temperature variation [16]. To evaluate the sensitivity of monolayer graphene based BK7 glass grating structure, we only increase the temperature from  23 C to  24 C and display its wavelength dependence of the GH shift at these two temperatures in figure 7.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…) to characterize the performance of the sensor, where DD r is the change of the GH value at the same l and DT is the value of temperature variation [16]. To evaluate the sensitivity of monolayer graphene based BK7 glass grating structure, we only increase the temperature from  23 C to  24 C and display its wavelength dependence of the GH shift at these two temperatures in figure 7.…”
Section: Results and Analysismentioning
confidence: 99%
“…Zhang et al achieved the control of the GH shift of the reflected beam from the surface of a colloidal ferromagnetic fluid by means of an external magnetic field [14]. Apart from the electric or magnetic field, the temperature is another alternative factor to regulate the GH shifts in various nanostructures [15][16][17]. Zang et al used a terahertz beam incident on the aluminum surface and observed that the magnitude of GH shift of this metal surface varies with temperature, whose maximum value is up to m 267.2 m [18].…”
Section: Introductionmentioning
confidence: 99%
“…A larger GHS corresponds to a larger evanescent wave as it propagates into the lower‐index medium near the interface. The characteristics and theoretical simulation of GHS and evanescent wave are still actively investigated although they are sometimes ignored because the exponentially small magnitude is far below that of the refracted field. However, the evanescent wave plays an important role in optical microcavities with a tubular geometry and thin walls (several micrometers or subwavelength thick).…”
Section: Light Propagation In Microtubular Cavitiesmentioning
confidence: 99%